Community-Driven Reconstruction in Colombia: An Experimental Study of Collective Action beyond Program Beneficiaries. (January 2018) - D'Exelle, Ben; Coleman, Eric; Lopez, Maria Claudia
Highlights: Communication increases cooperation, and this effect is stronger in groups with more cooperative peers. This peer effect is mainly driven by the behavior of CDR program beneficiaries. Non-beneficiaries are more influenced by beneficiaries than by non-beneficiaries. This difference in peer effects increases with social distance with the peers. Abstract: Increased community cooperation is an important objective of Community-Driven Reconstruction (CDR) programs in post-conflict settings. While these programs typically work with a limited group of beneficiaries, little is known about the potential community impact beyond these beneficiaries. To investigate this, we empirically analyze how cooperative behavior develops in a lab-in-the-field experiment with mixed groups of CDR program beneficiaries and non-beneficiaries, organized in 42 municipalities in Colombia with active CDR programs. In the experiment, we use two rounds of a binary public goods game with a communication stage between both rounds. The experimental data are complemented with information on pre-existing social proximity among the participants and whether they have participated in a CDR program. We find that cooperation increases after communication, and that it correlates positively with the proportion of cooperators before communication. This peer effect is mainly driven by the cooperative behavior of CDR program beneficiaries while the influence of non-beneficiaries is limited.